Conjugal Rights : Marriage, Sexuality, and Urban Life in Colonial Libreville, Gabon. - Jean-Baptiste, Rachel (New African histories series., 2014)
Conjugal Rights is a history of the role of marriage and other arrangements between men and women in Libreville, Gabon, during the French colonial era, from the mid-nineteenth century through 1960. Conventional historiography has depicted women as few in number and of limited influence in African colonial towns, but this book demonstrates that a sexual economy of emotional, social, legal, and physical relationships between men and women indelibly shaped urban life. Bridewealth became a motor of African economic activity, as men and women promised, earned, borrowed, transferr.